An Analysis Of Taboo Words Used In Extended Player Album “More Malice” Snoop Dogg - Jessy Ernes; Gurendi Wiwoho (Universitas 17 Agustus 1945 Semarang, 2022)
Communication is the way to associate with others. It is not only spoken but also can be written which can be expressed in text. Text could be a language that contains sentences that express someone’s feelings, thoughts, and messages. Song lyrics are one of the results of a text. It has meaning from the speaker to readers. In this study, the writer is interested to discuss taboo words in the song lyrics within More Malice EP by Snoop Dogg. Especially, this study focus on analyzing their types, the predominant types, their meanings and their functions. The research method used in this study is descriptive qualitative. There are 8 songs in the album, but only 7 songs were analyzed. Based on the analysis of the data of taboo words in the album, the results are as follows. Firstly the types of taboo words found in the album are epithet, vulgarity, obscenity, and profanity. The predominant type is obscenity. Secondly, the types of taboo words found in the album are conceptual, connotative, and affective. The predominant meaning is connotative. Finnaly, the functions of taboo words found in the album are to draw attention, to show contempt, to be provocative, and to mock authority. The predominant function is to draw attention. Keywords: semantics, taboo words, song lyrics, meanings, functions